The impact of previous action on bargaining: An experiment on the emergence of preferences for fairness norms - Thomas Neumann; Stephan Schosser; Bodo Vogt (Games, 2017)
The communication of participants to identify an acceptable bargaining outcome in the Nash bargaining game is all about fairness norms. Participants introduce fairness norms which yield a better outcome for themselves in order to convince the other participant of their bargaining proposal. Typically, these fairness norms are in line with theoretical predictions, which support a wide variety of different but fair outcomes the participants can choose from. In this experiment, we play two treatments of the Nash bargaining game: in one treatment, the participants play a dictator game prior to bargaining, and in the other treatment they do not. We find that participants who have not played the dictator game intensively discuss the outcome of the game and come to solutions closer to the equal split of the pie the longer they chat. This effect vanishes as soon as the participants have previous experience from a dictator game: instead of chatting, they establish the fairness norm introduced in the dictator game. Remarkably, if the dictator is unfair in the dictator game, he also gets a higher share of the pie in the Nash bargaining game.
Keywords: 330; bargaining game; dictator game; norms; experimental economics